The Blurring of Attractive Work Practices Across Health Care Sectors. (December 2013) - Rodwell, John J.; Demir, Defne
Magnet-style characteristics are considered important to the recruitment and retention of nurses. Little is known about nurses' perceptions of these characteristics across public, private, and third sector health care organizations. The primary aim of this paper is to examine these characteristics across sectors to determine whether differences in key Magnet-style characteristics exist. Given the employee-level focus, demographic factors were also considered. Australian nurses ( n = 459) were recruited using an online panel. No differences between sectors on work environment dimensions were found. Gender, age, employment type, and tenure revealed significant relationships with various work characteristics. Similarities in the work perceptions across sectors implies no specific sector will be differentially impacted by the increasing nurse shortages. An increasing emphasis on contemporary work environments will increase the presence of Magnet-like characteristics irrespective of sector. These results highlight the potential of practice permeability occurring, particularly in a system with common policy and operational drivers.